ENGINEERING MANAGEMENT OF MONITORING THE TECHNICAL READINESS OF GRAIN HARVESTER ON EFFICIENCY OF ITS MACHINE USE - Titova, L. L. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2023)
The article formulates the methodical principles of increasing the efficiency of the technical service of agricultural machinery of agro-industrial complex enterprises on the basis of its information support. The structure of district-level technical service was developed taking into account modern features, development prospects and requirements for material and technical support, maintenance and repair of agricultural machinery. On the basis of the conducted studies of the processes of movement and processing of internal information, it was considered appropriate to use the method of a combined questionnaire and sample survey for its selection. As for the method of selection of external information, in this case it is planned to conduct a selection based on the qualitative composition of information with the help of expert evaluations. The formation of the expert group was carried out according to the criterion of maximum coherence of opinions of its members, provided that the involved experts have a high degree of competence in subject field. In article, studies of the production activity of technical service enterprises are recommended to use local computer networks, which include an automated workplace of specialists, which allows for operational management of all links of the technical process of maintenance and repair of machines. Based on the developed methods, a software product was created for a quick search for the necessary and sufficient information for a specialist or a manager of a technical service enterprise.As a result of the implementation of the above-mentioned measures developed and implemented at technical service enterprises, the following practical results were obtained: the labor intensity during the first one decreased on average by 7.8%, during the second one by 8.2%, during seasonal repairs by 9%, and during current repairs by 22%. The obtained regularity of the dependence of the time spent on maintenance and repair on the completeness of information shows that the more complete the database is, the less time is spent on making decisions and carrying out work. Thus, on the basis of the research carried out in the article, it can be stated that when agricultural enterprises switch to a strategy of maintenance based on the condition of machines – on the basis of indiscriminate diagnostics and when using the developed methodology in technical service technologies, the labor intensity of all types of work can be significantly reduced, on average by 20–25%, and the failure rate of a component can be only 1%.